Edukasi Gizi Seimbang & ASI Eksklusif di Desa Wiyono Kabupaten Pesawaran - Nurul Aziza; William Arisandi; Shofiyyah Nur Aziza; Ni Kadek Widiti (STIKes Ibnu Sina Ajibarang, 2025)
Nutritional problems can occur due to two factors, namely direct factors and indirect factors. Direct factors are unbalanced nutritional intake and infectious diseases. The achievement of Exclusive Breastfeeding in Pesawaran Regency during 2014-2019 fluctuated. In 2014, babies who received exclusive breastfeeding were 30.19%, in 2015 it decreased to 20.85%, in 2016 it increased to 49.76% and in 2019 it was 50.48% and still below the expected national target of 80% 11. Based on the results of a pre-survey of 30 breastfeeding mothers, there were 17 mothers (56.6%) with an average age of 15-25 years and most of them with low levels of education who did not provide exclusive breastfeeding on the grounds that the mother worked and did not get support from her husband to provide exclusive breastfeeding (Pesawaran Regency Health Office). The purpose of this community service activity is to increase mothers' knowledge about fulfilling balanced nutrition and exclusive breastfeeding so that toddlers are free from stunting.